KEBIJAKAN PROGRAM UJI KOMPETENSI DALAM MENINGKATKAN PROFESIONALISME WARTAWAN DI KOTA SUKABUMI - akasah , Muhammad (Mimbar Administrasi Mandiri, 2024)
The Journalist Competency Test Program carried out by the Press Council is one way to increase the professionalism of journalists. This is in line with Press Council Regulation No. 1 of 2010 concerning journalist competency standards which states that only journalists can take the journalist competency test (UKW), which aims to uphold press freedom based on the public interest, as well as to maintain the honor and dignity of journalism as a profession of intellectual work, as well as avoiding misuse of the journalist profession through journalist competency tests. Based on research on the behavior of journalists in the city of Sukabumi, it shows that many people claim to be journalists but do not demonstrate journalist standards, which is detrimental to various parties and detrimental to the journalist profession which is tarnished by the actions of fake journalists. A journalist competency test is very necessary to show that journalists can actually show a competency card after carrying out a journalist competency test so that ultimately the public can assess which journalists meet journalist standards or which do not. The need for a journalist competency test is in line with the statement of expert Muhamad Nuh (former Minister of Education and Culture and Chairman of the Press Council), that the Journalist Competency Test (UKW) is a requirement to improve quality in the press world.